Seasonal Changes in Microbial Communities Associated With the Jewel Anemone Corynactis viridis - Palladino, Giorgia; Biagi, Elena; Rampelli, Simone; Musella, Margherita; D’Amico, Federica; Turroni, Silvia; Brigidi, Patrizia; Luna, Gian Marco; Candela, Marco (Frontiers in Marine Science, 2021)
Increasing evidence indicates that host-associated microbial communities play a key role in the biology of marine eukaryotic organisms. Amongst them, Corallimorpharia are extensively found on reefs, carpeting vast reef areas, where they can exert important roles as habitat forming holobionts, being at the base of complex trophic webs. Here we explore the bacterial community structure, and its changes across different seasons, associated with the jewel anemone Corynactis viridis, an anthozoan Cnidaria that is widely distributed in the northeastern Atlantic Ocean and the Mediterranean Sea. Samples were collected in the North Adriatic Sea in three seasons and the community composition was studied using 16S rDNA sequencing. We show that C. viridis-associated microbial communities are unique and significantly different from those in the surrounding seawater. Interestingly, we observe remarkable changes in the C. viridis microbiome according to seasonality. In particular, the C. viridis microbiome is capable of rearranging its overall ecological structure with the winter-summer transition, moving from an oligotrophic anaerobic community to a heterotrophic ecosystem, with the propensity to ferment proteins and complex polysaccharides. Our findings demonstrate that C. viridis has a unique associated microbiota and suggest that this is capable of adapting to seasonal changes in the host physiology, by establishing a microbiome-host interaction process whose relevance to C. viridis has yet to be determined.